Katalis Perubahan: Potensi Pemuda Lokal Dalam Membangun Keberlanjutan Melalui Realisasi Ekonomi Hijau - Christabel, Bernice (UIN ALAUDDIN MAKASSAR, 2024)
In confronting the increasingly severe global environmental challenges, the urgency of transitioning towards a green economy intensifies. This research emphasizes the role of local youth as catalysts in driving such changes by examining the interplay between global environmental norms and local dynamics through a constructivist lens. The study aims to identify and analyze the impact of empowering youth in the implementation of green economies, as well as the obstacles they encounter in this process. Employing qualitative and descriptive research methods, this study enables a thorough understanding of the social and economic dynamics that influence youth participation in the green economy. The discussion addresses the challenges faced by local youth, outlining them alongside strategies that could enhance their capacity to contribute effectively. Additionally, the study introduces several case studies from various countries that have successfully implemented green economy models which could be adapted and applied in Indonesia. The research underscores the importance of integrating youth in the planning and execution of green economy policies. This is not only crucial for ensuring long-term sustainability but also for ensuring that development processes are effective, inclusive and participatory.